2000
DOI: 10.1093/humrep/15.10.2165
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of hyper-, hypohaploidy and diploidy in ejaculate, epididymal and testicular germ cells of infertile patients

Abstract: The hypothesis that sperm aneuploidy and diploidy increase as a function of spermatogenesis impairment was addressed. Ejaculated semen samples from a series of men (n = 22) with very low total normal motile count (1 x 10(6)) was analysed in terms of sperm aneuploidy and diploidy by in-situ hybridization and compared with controls (n = 10). Germ cell aneuploidy was also analysed in an additional series of infertile patients presenting unexplained infertility (n = 3), congenital absence of the vas deferens (CAVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
68
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 28 publications
12
68
2
Order By: Relevance
“…20 This study has shown that patients with OA or NOA have a high rate of numerical chromosome abnormalities in spermatozoa extracted from the epididymis or the testis respectively, confirming recent preliminary results. 7,21 Thus these data extend the high aneuploidy rate found in ejaculated spermatozoa of infertile men with various degree of semen abnormalities (which others and ourselves have demonstrated 3 ± 11, ) to spermatozoa extracted from the epididymes or the testes of patients with azoospermia.…”
Section: Discussionsupporting
confidence: 79%
“…20 This study has shown that patients with OA or NOA have a high rate of numerical chromosome abnormalities in spermatozoa extracted from the epididymis or the testis respectively, confirming recent preliminary results. 7,21 Thus these data extend the high aneuploidy rate found in ejaculated spermatozoa of infertile men with various degree of semen abnormalities (which others and ourselves have demonstrated 3 ± 11, ) to spermatozoa extracted from the epididymes or the testes of patients with azoospermia.…”
Section: Discussionsupporting
confidence: 79%
“…26,67 The majority of aneuploidy studies in sperm from infertile men report around a threefold increase in sperm aneuploidy levels compared to controls, with levels of up to 10-fold being reported; predominantly for severe infertility (severe oligoasthenoteratozoospermia and azoospermia). 68,69 There are a few case reports of extraordinarily high levels of aneuploid and polyploid sperm (50-100%) in individuals with a high proportion of macrocephalic, multinucleated and multiflagellate sperm. [70][71][72][73] It perhaps counterintuitive but there is little or no evidence to suggest that there is a preferential selection of chromosomally normal sperm for fertilization.…”
Section: The Relationship Between Chromosome Aneuploidy and Male Infementioning
confidence: 99%
“…Chromosomal abnormalities have been extensively found in the spermatozoa of many infertile men (17)(18)(19)(20)(21). The incidence of chromosomal structural aberrations increases among patients undergoing ICSI programs than those on IVF programs (20,21).…”
Section: Introductionmentioning
confidence: 99%